Walter Benjamin, politics, and bodily collectivity: from Leib and Körper to anthropological materialism - Jesien, Karolina (2025)
This thesis explores Walter Benjamin’s concept of bodily collectivity and its evolution in relation to emancipation and social change in the interwar period. It traces this development from his early work on the body understood as Leib and Körper and through its reformulation within the framework of anthropological materialism from the late 1920s onwards. The focus of this analysis is on the development of these ideas in light of Benjamin’s changing approach to revolutionary politics. Contrary to readings that emphasise the melancholic aspect of his philosophy of history, this analysis focuses on Benjamin’s unwavering belief in the transformative potential of collective human existence. The thesis argues that Benjamin’s reflection on the human body as both a site of historical transformation and a locus for political emancipation reveals his long-standing interest in the emerging planetary scale of human collectivity and the underlying potential for the reorganisation of social relations entailed in it. Ultimately, this study underscores the complexity of Benjamin’s vision of bodily collectivity and offers the first monographic treatment of its evolution.